2021
DOI: 10.1039/d1bm01127h
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment and nanotherapeutics: intruding the tumor fort

Abstract: The tumor microenvironment is an obstructive fort that hinders the delivery of drugs. Manipulating this fort using nanoparticle-based strategies could aid in effectively managing tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 284 publications
0
29
0
Order By: Relevance
“…The maximal fluorescence signal was observed at 6 h post injection, and considerable enrichment at the tumour sites could remain for 10 h. These results suggested that NP-DNs could specifically accumulate in tumours, possibly due to the enhanced permeation and retention (EPR) effect. 52,53…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximal fluorescence signal was observed at 6 h post injection, and considerable enrichment at the tumour sites could remain for 10 h. These results suggested that NP-DNs could specifically accumulate in tumours, possibly due to the enhanced permeation and retention (EPR) effect. 52,53…”
Section: Resultsmentioning
confidence: 99%
“…The maximal fluorescence signal was observed at 6 h post injection, and considerable enrichment at the tumour sites could remain for 10 h. These results suggested that NP-DNs could specifically accumulate in tumours, possibly due to the enhanced permeation and retention (EPR) effect. 52,53 The antitumor efficacy of NP-DNs was then determined in tumour-bearing nude mice. The mice were randomly assigned to 3 groups (n = 5) and intravenously injected with PBS, NP-DNs (10 mg kg −1 ), or NP-DNs (10 mg kg −1 ) with Fer-1 (1 mg kg −1 ).…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…Recently, stimuli-responsive nanoparticles have also been proposed as a promising active targeting strategy for tumor treatment [ 18 22 ]. Specifically, an acidic environment, high levels of reactive oxygen species (ROS) and glutathione (GSH), and overexpression of specific enzymes in the tumor microenvironment (TME) can contribute to the development of stimuli-responsive nanoparticles for targeted drug delivery, as these nanoparticles maintain their stealth features in the normal physiological environment but upon homing to targeted sites or the local microenvironment are responsive and release encapsulated agents [ 18 21 ]. Moreover, functionalized nanoparticles can also be activated by external stimuli including magnetic fields, light, and ultrasound, to realize efficient tumor accumulation and controlled drug release in a temporal and spatial-specific fashion [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanodrugs can specifically aggregate at the tumor site due to the enhanced permeability and retention (EPR) effect, [ 8 ] and through appropriate modifications, nanoparticles (NPs) can achieve active targeting to tumors. Moreover, nanodrugs can result in sustained release and circulation in blood, reducing toxicity and side effects and can also maintain the integrity and biological activity of the drug.…”
Section: Introductionmentioning
confidence: 99%